1996
DOI: 10.1002/hep.510240201
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for the grading of activity in chronic hepatitis C

Abstract: FOR THE METAVIR COOPERATIVE STUDY GROUP histological classification of chronic hepatitis, and several Histological activity reflects the global assessment of propositions have recently been made by different groups of basic necroinflammatory lesions and is a criterion of mapathologists. [4][5][6][7] A consensual proposition was to separately jor importance in chronic hepatitis C. The aim of this assess, using scoring systems, the degree of liver fibrosis and study was to propose and test the accuracy of a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
2,501
4
44

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,660 publications
(2,613 citation statements)
references
References 14 publications
22
2,501
4
44
Order By: Relevance
“…Tsochatzis and colleagues found an inverse association between resistin levels and the severity of fibrosis (according to Ishak) in chronic viral hepatitis; and a nearly significant trend towards higher resistin levels in patients with HCV genotype-3 compared to other genotypes [24,46]. Tiftikci et al confirmed the finding of higher resistin levels in HCV patients with limited fibrosis (METAVIR scoring system), but found no association to HCV genotype [25,47]. More recently, Baranova and co-workers reported a clear association between HCV genotype-3 and raised resistin levels compared to patients with non-genotype-3 infection [26].…”
Section: Discussionmentioning
confidence: 95%
“…Tsochatzis and colleagues found an inverse association between resistin levels and the severity of fibrosis (according to Ishak) in chronic viral hepatitis; and a nearly significant trend towards higher resistin levels in patients with HCV genotype-3 compared to other genotypes [24,46]. Tiftikci et al confirmed the finding of higher resistin levels in HCV patients with limited fibrosis (METAVIR scoring system), but found no association to HCV genotype [25,47]. More recently, Baranova and co-workers reported a clear association between HCV genotype-3 and raised resistin levels compared to patients with non-genotype-3 infection [26].…”
Section: Discussionmentioning
confidence: 95%
“…The duration of HCV infection was estimated from the time of occurrence of a potential risk factor for HCV infection (i.e., blood transfusion, injection drug use or tattooing) to the time of B-NHL diagnosis. Liver fibrosis was evaluated via liver biopsy establishing a METAVIR score [17] and when not available by noninvasive elastometry [18].…”
Section: Study Design and Participants Between November 2006 And Novmentioning
confidence: 99%
“…Biopsies were performed in 21 out of 42 liver transplant recipients at time of elevation of liver enzymes. All biopsies were evaluated for extent of inflammation and fibrosis and scored using the METAVIR system [30].…”
Section: Patients and Samplesmentioning
confidence: 99%